Development of a mathematical model to monitoring the velocity of subsidence of charge material column in the blast furnace based on the parameters of gas pressure in the furnace tract - Kravchenko, V.; Vorotnikova, Z.; Simkin, O. I.; Koyfman, O. O.; Кравченко, В. П.; Воротнікова, З. Є.; Сімкін, О. І.; Койфман, О. О. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР"; Український державний університет залізничного транспорту, 2022)
A problem of estimating the velocity of subsidence of a column of charge materials using non-contact methods was considered. This is important because the level of furnace charge materials and the velocity of their subsidence are main indicators of melting intensity determining the furnace productivity.The design of a blast furnace and its blast path were described and existing methods and means of controlling the velocity of charge materials in the blast furnace were analyzed. A mathematical model was presented for estimating the velocity of subsidence of charge materials in a blast furnace based on the magnitude and fluctuations of gas pressure along the furnace shaft height. The model is based on the fact that the furnace gases rise up in the furnace shaft through elementary channels in the column of charge materials consisting of a combination of capacitances and resistances. Volume of capacities and values of resistance of elementary channels are constantly changing. This changes hydraulic resistance to gas movement in the blast furnace. The system of differential equations describes the dependence of the amplitude of pressure fluctuations on the amplitude of change in coefficients of resistance and frequency of pressure fluctuations on the frequency of change in coefficients of resistance. The experimental data on velocity of the column of charge materials and fluctuations in the pressure differential in the furnace were processed and their significant relationship was shown to confirm the previous theoretical study results. To assess the model adequacy, the simulation method was used. The results of the simulation model work were confirmed by experimental data.The developed mathematical model can be introduced into production. This will make it more economical and safer through better and more predictable control and improved flexibility in operation under different production conditions

Розглянуто задачу оцінки швидкості опускання стовпа шихтових матеріалів за допомогою безконтактних методів. Це важливо, тому що рівень шихтових матеріалів печі і швидкість їх сходу є одним з основних показників інтенсивності плавки, що визначає продуктивність печі. Описано конструкцію доменної печі і її дуттєвий тракт, проаналізовано існуючі методи та засоби контролю швидкості руху шихтових матеріалів у доменній печі. Представлено математичну модель оцінки швидкості опускання шихтових матеріалів у доменній печі на підставі величини і коливань тиску газів по висоті шахти печі. Модель заснована на тому, що в шахті печі горнові гази піднімаються вгору по елементарним каналах стовпа шихтових матеріалів, які складаються з сукупності ємностей і опорів. Довжини ємностей і обсяги опорів елементарних каналів постійно змінюються, змінюючи гідравлічний опір руху газів в доменній печі. Даний процес описаний системою диференціальних рівнянь, яка в сталому режимі перетворюється в систему лінійних рівнянь. Система описує залежність амплітуди коливань тисків від амплітуди зміни коефіцієнтів опору і частоти коливань тисків від частоти зміни коефіцієнтів опору. Опрацьовано експериментальні дані швидкості руху стовпа шихтових матеріалів і коливань перепаду тиску в печі, показано їх значущий зв'язок, що підтверджує попередньо отримані теоретичні результати. Для оцінки адекватності моделі застосовується метод імітаційного моделювання. Результати роботи імітаційної моделі підтверджуються експериментальними даними.
Keywords: blast furnace; blast path; mathematical model; adequate estimate; experimental data; доменна піч; доменний тракт; математична модель; адекватна оцінка; експериментальні дані